An evaluation of government-backed loan scheme in Malaysia - Mohd. Noor Mohd. Shariff (Universiti Utara Malaysia Press, 2003)
SMEs are considered to be an engine for growth in both developed and developing countries. Government-backed loan schemes thus play a major role to enable SMEs to have access to credit facilities. This work investigates the schemes offered in Malaysia by Credit Guarantee Corporation (CGS). It examines the appropriateness of its main financing instrument, the New Principles Guarantee Scheme (NPGS) to the financing needs of SMEs.